2020
DOI: 10.3390/jcs4030131
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive and mechanical Behavior of CNT based polyurethane foam

Abstract: Carbon nanotubes (CNT) embedded into a polymeric foam demonstrate an enhancement in electrical and mechanical properties of the final nanocomposite. The enhanced material with new characteristics, e.g., piezoresistivity, can be substituted with the traditional metallic material to design sensors, switches, and knobs directly into a single multifunctional component. Research activities in this field are moving towards a mono-material fully integrated smarts components. In order to achieve this goal, a simple me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…If the composite material becomes electrically conductive, it can be used in new applications, in which electrical properties are required, such as antistatic or static dissipation, conductive and electromagnetic shielding materials [4]. Among the carbon fillers to be dispersed in polymers, CNTs and graphene have the most notable effect on electrical conductivity, with an electrical percolation threshold ranging between 1 and 4 wt.% [6][7][8][9][10][11][12], while a higher filler loading (c.a. 4-15 wt.%) is usually required to obtain an electrical percolated network with graphite-based materials (graphite flakes, graphite nanoplatelets, expanded graphite, nanographite) [13][14][15], carbon fibers [16], and carbon black [11,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…If the composite material becomes electrically conductive, it can be used in new applications, in which electrical properties are required, such as antistatic or static dissipation, conductive and electromagnetic shielding materials [4]. Among the carbon fillers to be dispersed in polymers, CNTs and graphene have the most notable effect on electrical conductivity, with an electrical percolation threshold ranging between 1 and 4 wt.% [6][7][8][9][10][11][12], while a higher filler loading (c.a. 4-15 wt.%) is usually required to obtain an electrical percolated network with graphite-based materials (graphite flakes, graphite nanoplatelets, expanded graphite, nanographite) [13][14][15], carbon fibers [16], and carbon black [11,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the new structure, these PRSs can monitor both short and long human movements that derive from the nano crack joint sensing mechanism and physical contact of conductive interconnected networks. De Meo et al ( 2020 ) used CNT embedded into a polymeric foam (PU) that showed an increase in electrical and mechanical properties. They manufactured three kinds of PRSs based on PU-CNT foam, (i) PU-CNT 1.5%, (ii) PU-CNT-COOH 1.0%, and (iii) PU-CNT-COOH 1.5%.…”
Section: Nanomaterials For Wearable Piezoresistive Sensorsmentioning
confidence: 99%
“…Science and industry are interested in polyurethanes (PU) because of their advantageous physical and chemical properties and the possibility of changing their structure depending on the intended use. Due to the fact that polyurethanes are one of the most versatile materials in the world today, they have many uses such as wall insulation, thermoplastic polyurethane roofs and floor coatings, automotive interior coatings, aerospace coatings, adhesives, fillers, and medical devices [2][3][4].…”
Section: Introductionmentioning
confidence: 99%